Terebellidae (Polychaeta: Terebellida) from the Grand Caribbean region - Londoño-Mesa, Mario H. (Zootaxa, 2009)
Twenty-four genera of Terebellidae Grube, 1850, are described including one new genus and forty-four species recorded and characterized from the Grand Caribbean region. Six species are newly described: Lysilla caribe sp. nov., Polycirrus angeli sp. nov., Eupolymnia rullieri sp. nov., Euthelepus kritzleri sp. nov., Streblosoma tenhovei sp. nov., and Kritzlerius anomalus gen. nov. and sp. nov. Twenty-four formerly recorded species are regarded as valid: Biremis blandi Polloni, Rowe & Teal, 1973, Enoplobranchus sanguineus Verrill, 1873, Polycirrus holthei Londoño-Mesa & Carrera-Parra, 2005, P. pennulifera Verrill, 1900, P. purpureus Schmarda, 1861, Amphitritides bruneocomata (Ehlers, 1887), Eupolymnia crassicornis (Schmarda, 1861), Lanicola carus (Young & Kritzler, 1987), L. garciagomezi (Londoño-Mesa, 2006), Loimia minuta Treadwell, 1929, L. salazari Londoño-Mesa & Carrera-Parra, 2005, Neoamphitrite glasbyi LondoñoMesa & Carrera-Parra, 2005, P. palmata (Verrill, 1873), P. sombreriana McIntosh, 1885, Polymniella aurantiaca Verrill, 1900, Scionides reticulata (Ehlers, 1887), Spinosphaera carrerai Londoño-Mesa, 2003, S. hutchingsae Londoño-Mesa, 2003, Terebella turgidula Ehlers, 1887, T. verrilli Holthe, 1986, Terebellobranchia mchughae Londoño-Mesa & CarreraParra, 2005, Streblosoma hartmanae Kritzler, 1971, S. polybranchia Verrill, 1900, Thelepus haitiensis Treadwell, 1931, and T. pascua (Fauchald, 1977). Two species are reinstated: Loimia bermudensis Verrill, 1900, and Thelepus crassibranchiatus Treadwell, 1901. One species is reinstated with a new combination: Eupolymnia magnifica (Webster, 1884). Five species names are new combinations: Pista cetrata (Ehlers, 1887), Pistella papillosa (Tourtellotte & Kritzler, 1988), Terebellobranchia hiata (Treadwell, 1931), Thelepus tenuis (Verrill, 1900), and T. verrilli (Treadwell, 1911). Finally, five species are regarded as distinct but remain undescribed because of the poor condition of the specimens: Amaeana sp. 1, Neoleprea sp. A Kritzler, 1984, Neoleprea sp. 1, Proclea sp. 1, and Thelepus sp. 1. All of the type and non-type material available for each species from the region is revised and compared with specimens of species previously regarded as junior synonyms of others species described from areas outsie of the region. A key to all species is provided.